2017
DOI: 10.3906/fiz-1610-35
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mg doping in the structural, optical, and electrical characteristics of ZnO-based DSSCs

Abstract: ZnO-and Mg-doped ZnO samples are prepared by spray pyrolysis on conducting glass substrates to fabricate ZnO-based dye-sensitized solar cells (DSSCs). Influences of Mg-doping content on the power conversion efficiencies of ZnO-based DSSCs are investigated. X-ray diffraction results show that all the samples exhibit a hexagonal wurtzite structure. Scanning electron microscopy data indicate that the ZnO sample has uniform rods with 1 µ m diameter.With respect to ZnO, the band gap value of 4 at.% Mg-doped ZnO sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The process parameters can easily be controlled using the chemical bath deposition process, which make it an excellent method for the fabrication of nanorods. The doping of ZnO with a second group including magnesium, calcium, beryllium, and strontium elements has been considered as an effective technique to varying the structural, optical, and electrical properties of ZnO [24][25][26]. Majeed Gul [27] et al reported the band-gap tuning of ZnO nanorods by the addition of Mg from 3.18 eV to 3.32 eV.…”
Section: Introductionmentioning
confidence: 99%
“…The process parameters can easily be controlled using the chemical bath deposition process, which make it an excellent method for the fabrication of nanorods. The doping of ZnO with a second group including magnesium, calcium, beryllium, and strontium elements has been considered as an effective technique to varying the structural, optical, and electrical properties of ZnO [24][25][26]. Majeed Gul [27] et al reported the band-gap tuning of ZnO nanorods by the addition of Mg from 3.18 eV to 3.32 eV.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore the bandgap values of Mg-doped ZnO of our samples increase with increases in Mg doping level. And this increase in the bandgap value corresponds to a rise in the e ciency of the fabricated DSSCs[36]. It absorbs the high energy of photons on the surfaces.…”
mentioning
confidence: 99%